Infraspecific variation within and across complete organellar genomes and nuclear ribosomal repeats in a moss - Lewis, Lily R.; Liu, Yang; Rozzi, Ricardo; Goffinet, Bernard (My University, 2016)
Bryophytes (mosses, liverworts, and hornworts) are diverse and ecologically and evolutionarily significant yet genome scale data sets and analyses remain extremely sparse relative to other groups of plants, and are completely lacking at the infraspecific level. By sequencing the complete organellar genomes and nuclear ribosomal repeat from seven patches of a South American sub-Antarctic neo-endemic non-model moss, we present the first characterization of infraspecific polymorphism within and across the three genomic compartments for a bryophyte. Diversity within patches is accounted for by both intraindividual and interindividual variation for the nuclear ribosomal repeat and plastid genome, respectively. This represents the most extensive infraspecific genomic dataset generated for an early land plant lineage thus far and provides insight into relative rates of substitution between organellar genomes, including high rates of nonsynonymous to synonymous substitutions. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: genomics; infraspecific polymorphism; early land plant; bryophyte; tetraplodon